2020
DOI: 10.1038/s41598-020-66223-2
|View full text |Cite
|
Sign up to set email alerts
|

NTAL is associated with treatment outcome, cell proliferation and differentiation in acute promyelocytic leukemia

Abstract: non-t cell activation linker (ntAL) is a lipid raft-membrane protein expressed by normal and leukemic cells and involved in cell signaling. in acute promyelocytic leukemia (ApL), ntAL depletion from lipid rafts decreases cell viability through regulation of the Akt/PI3K pathway. The role of NTAL in APL cell processes, and its association with clinical outcome, has not, however, been established. Here, we show that reduced levels of ntAL were associated with increased all-trans retinoic acid (AtRA)induced diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Interestingly, a more discrete anti-tumorigenic effect was observed in NB4-R2 cells (ATRA-resistant). This could be explained by the more aggressive phenotype observed on this cell line in comparison with the parental counterpart (NB4 cells) [30] Intriguingly, the knock-down of SLIT2 appeared to execute a more prominent effect than the peptide treatment, arguing that SLIT2 carries out not solely receptor mediated functions, but also important intracrine signaling worth further exploration.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, a more discrete anti-tumorigenic effect was observed in NB4-R2 cells (ATRA-resistant). This could be explained by the more aggressive phenotype observed on this cell line in comparison with the parental counterpart (NB4 cells) [30] Intriguingly, the knock-down of SLIT2 appeared to execute a more prominent effect than the peptide treatment, arguing that SLIT2 carries out not solely receptor mediated functions, but also important intracrine signaling worth further exploration.…”
Section: Discussionmentioning
confidence: 89%
“…We have demonstrated that NTAL downregulation is associated with reduced cell viability and proliferation in APL and also leading to decreased tumor burden in vivo xenograft models of mantle cell lymphoma and leukemia (9,30). Here, we further extended our study of NTAL in AML, initially evaluating NTAL gene expression between several neoplastic cell lines using the Cancer Cell Line Encyclopedia.…”
Section: Discussionmentioning
confidence: 95%
“…A, sections of U937 (CT and NTAL-KD) tumors stained with hematoxylin and eosin or immunostained for NTAL. B, tumor masses derived after 2 weeks: U937: CT (1.073 g ± 0.1486) and NTAL-KD (0.5975 g ± 0.1506) (n = 4, p = 0.0287, 95% confidence interval) and NB4: CT (1.286 g ± 0.3137) and NTAL-KD (0.8540 g ± 0.3402) (n = 5, p = 0.0143, 95% confidence interval) ( * data published) (9). C, Western blotting analysis of total tumor protein extracts from engrafted tumors for NTAL, procaspase-3, p-Akt (Ser-473), Akt, Ras, p-p44/42 MAPK, and p44/42 MAPK (animals A1 = 1, A2 = 2, and A3 = 3).…”
Section: Analysis Of the Subcellular Localization Of Ntal Interactorsmentioning
confidence: 95%
See 2 more Smart Citations